2019
DOI: 10.18280/ijht.370210
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to the Simulation and Parametric Analysis of the Operation of a Solar Concentration Thermal Installation

Abstract: The objective of this contribution is to highlight the direction of variation in thermal efficiency in order to determine the optimum thermodynamic parameters for the best operation of the solar concentrating heat machine. The machine studied as part of this article works in part following the ideal cycle of RANKINE and other part by following the ideal cycle of HIRN (improved installation). The preferred approach to achieve the objectives is based on: − Influence of low pressure and high pressure for a machin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Besides the practical functions, architects of modern residences pay more and more attention to the expression of the internal space to create an external shape with concavity and convexity [10]. In this case, such components as balconies, bay windows, and outdoor AC unit spaces become active elements, playing a key role in diversifying the building faç ade and creating nuances of gradations.…”
Section: Extension As a Protruding Elementmentioning
confidence: 99%
“…Besides the practical functions, architects of modern residences pay more and more attention to the expression of the internal space to create an external shape with concavity and convexity [10]. In this case, such components as balconies, bay windows, and outdoor AC unit spaces become active elements, playing a key role in diversifying the building faç ade and creating nuances of gradations.…”
Section: Extension As a Protruding Elementmentioning
confidence: 99%
“…Luo et al [16] developed a modified model to do a parametric analysis of the operation of a Solar Concentration installation in order to propose a possible improvement. Several review papers have been reported in the literature focusing on experimental and numerical investigations with parabolic trough power plants around the World [17][18][19][20][21][22][23][24][25].…”
Section: Previous Modeling and Simulation Studiesmentioning
confidence: 99%
“…In response to these problems, the government began to adopt policies and corresponding technical regulations, and designers and real estate developers gradually launched the engineering operation. Hence, the initial idea of integrating solar water heaters with buildings was conceived, leading to the development of intelligent integrated design advancing to its second phase, known as the stage of basic overlay [6].Later, through consultations with solar developers, real estate developers began designing solar products with a modular mechanism [7]. As a result, solar water heaters have overcome technical and structural problems and could be perfectly integrated into buildings.…”
Section: Introductionmentioning
confidence: 99%